Experiments on long-term and short-term memory for pitch in musicians - RAKOWSKI, Andrzej; ROGOWSKI, Piotr (Archives of Acoustics, 2007)
A series of experiments on the memory for pitch was performed with 18 musicians. They had to pass a pitch-naming and a newly-designed pitch-producing test meant to check their passive and active absolute-pitch ability. On that ground two of them, who revealed faultless, full absolute pitch and one who had most typical relative (non-absolute) pitch, were selected to take part in a case-study-type experiment on short-term memory for pitch. The experiment partly confirmed the previous finding (Rakowski, [5]) of the about 2-minute time range for short-term pitch memory in relative-pitch listeners. It also explained cases in which absolute-pitch possessors, when required to repeat after short-term delay an external pitch standard, either use for that purpose their authentic short-term memory for pitch, or rather relay on comparisons with their absolute-pitch standards.